2020
DOI: 10.1007/s40201-020-00494-9
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant addition in diesel oil degradation – how can it help the microbes?

Abstract: Purpose Despite wide research on bioremediation of hydrocarbon-contaminated soil, the mechanisms of surfactant-enhanced bioavailability of the contaminants are still unclear. The presented study was focused on the in-depth description of relationships between hydrocarbons, bacteria, and surfactants. In order to that, the biodegradation experiments and cell viability measurements were conducted, and the properties of cell surface were characterized. Methods MTT assay was employed to measure plant extracts toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…We attribute that the inhibitory effect of TPH degradation in SDS concentration at 5 CMC may be due to the formation of structural chemical complexes that inhibit microbial growth that affects the biodegradation of TPH, a behavior that has also been reported in studies by Zarei and Fazaelipoor (2022). The inhibitory effect at 9 CMC of Triton X-100 may be due to the dissolution process being affected as well as that the bacterial biodegradation activity probably due to an excess of micelles of the contaminant (Zdarta et al, 2020). Other studies have reported that the addition of Triton X-100 at high concentrations (360 mg/L) to the system with diesel oil affected the hydrophobicity of the cell surface, causing the microorganisms to be unable to adhere to the surface of the hydrocarbon (Kaczorek et al, 2010).…”
Section: Biodegradation Of Tph At the Microcosm Levelsupporting
confidence: 63%
“…We attribute that the inhibitory effect of TPH degradation in SDS concentration at 5 CMC may be due to the formation of structural chemical complexes that inhibit microbial growth that affects the biodegradation of TPH, a behavior that has also been reported in studies by Zarei and Fazaelipoor (2022). The inhibitory effect at 9 CMC of Triton X-100 may be due to the dissolution process being affected as well as that the bacterial biodegradation activity probably due to an excess of micelles of the contaminant (Zdarta et al, 2020). Other studies have reported that the addition of Triton X-100 at high concentrations (360 mg/L) to the system with diesel oil affected the hydrophobicity of the cell surface, causing the microorganisms to be unable to adhere to the surface of the hydrocarbon (Kaczorek et al, 2010).…”
Section: Biodegradation Of Tph At the Microcosm Levelsupporting
confidence: 63%
“…The common explanation for this question is that biosurfactants can increase the solubility, which can result in higher growth of bacteria and greater efficiency of biodegradation [ 124 ]. However, more-comprehensive analysis of this process has been carried out taking into account multilevel changes occurring in cells from the genome, through metabolic activity, to the surface properties of the cells [ 125 ]. These focused on the in-depth description of relationships between hydrocarbons and bacteria and found changes in the genome caused by exposure to surfactants.…”
Section: Microbial Communitymentioning
confidence: 99%
“…More and more studies focus on supporting the bioremediation process by using various environmentally safe amendments, such as biosurfactants [ 19 , 20 , 21 , 22 , 23 ], or the use of microbial combined methods, including fungi [ 24 , 25 , 26 , 27 ], plants [ 28 , 29 , 30 , 31 , 32 ], algae [ 33 ], biochar [ 34 , 35 ], and biofilms [ 36 ]. γ-polyglutamic acid (PGA) may be one such amendment with great potential for use in the process of pollutant remediation.…”
Section: Introductionmentioning
confidence: 99%